2022
DOI: 10.1108/jd-12-2021-0236
|View full text |Cite
|
Sign up to set email alerts
|

The things we carry: migrants' personal collection management and use

Abstract: PurposeThis paper explores personal collection management and use in the context of migration. The paper further investigates how migrants use items in personal collections to reflect their self-identity and learn about their heritage.Design/methodology/approachInterviews were used to collect data from 14 immigrants in New Zealand.FindingsFindings show how migrants perceive the value of their personal collections, manage their personal collections during migration and use their personal collections as instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Findings also revealed that early‐career researchers employed various PIM practices after completing the information seeking phase to navigate academic transitions. These practices helped them maintain personal information over the long term (Krtalić & Ihejirika, 2022) and gain a sense of control over their information items (Alon & Nachmias, 2020; Kaye et al, 2006). As the transition progressed, the PIM practices became more refined and hierarchical, reflecting the increasing need for organization and planning.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also revealed that early‐career researchers employed various PIM practices after completing the information seeking phase to navigate academic transitions. These practices helped them maintain personal information over the long term (Krtalić & Ihejirika, 2022) and gain a sense of control over their information items (Alon & Nachmias, 2020; Kaye et al, 2006). As the transition progressed, the PIM practices became more refined and hierarchical, reflecting the increasing need for organization and planning.…”
Section: Discussionmentioning
confidence: 99%
“…We note above that individuals and institutions accumulate digital file collections of extensive scale and variety. For individuals, collections contain a variety of everyday items such as private photos, family plans and finances, professional activities, and information reflecting many other of life’s activities and tasks (Dinneen & Julien, 2019; Jones et al, 2017; Krtalić & Ihejirika, 2022). Accumulated over years or a lifetime, these digital assets can have long‐term value for family members, and the collections of culturally significant people can also have value for society in the form of cultural heritage (Krtalić et al, 2021).…”
Section: Collection Annotation Assistantmentioning
confidence: 99%
“…Informacijske potrebe migranata daleko su češće istraživane u odnosu na zemlju doseljenja nego na zemlju iseljenja. No migranti imaju potrebu biti informi-rani o zbivanjima u domovini, održavati kontakte te proširivati znanja o kulturi kako bi stabilizirali osjećaj povezanosti i identiteta (Krtalić and Ihejirika, 2022). Te potrebe uočene su ne samo kod prve generacije migranata nego i kod njihovih potomaka i šire obitelji.…”
Section: Informacijske Potrebe I Usluge U Odnosu Na Domovinuunclassified